Attitude of athletes to availability, accessibility and utilization of information and communication technology for increased sports performance among Nigerian universities (2015)
Information and Communication Technology (ICT) in sports is the knowledge and application of using specialized equipment and the latest modern technologies to perform tasks more efficiently. Literature review found there are rare successful instructional cases of integrating information technology into sport currently in Nigeria. Majority of the published research concentrated on the development of software or on the design of interactive learning platforms without assessing their influence on sport performance. However, in Nigeria, despite the huge potential offered by ICT, the actual use for improved sport performance among athletes seems low Therefore, this study examined Attitude of Athletes to Availability, Accessibility and Utilization of ICT tools for increased Sports Performance in Nigerian Universities. Four research questions were raised and answered in the stud}’. The study adopted non-experimental descriptive survey design. Multistage sampling techniques were used to select 18 Universities from Federal, State and Private, ten sports and 1,800 athletes. Simple random sampling technique was used to select one Federal, State and Private from the six geo-political zones. Three instruments were used to elicit information from respondents. Data collected was subjected to statistical analysis using both descriptive and inferential statistics. The result shows that athletes in Nigeria Universities were aware of what ICT is all about and their attitude to its integration into sport is positive (1,152 or 64.0%) and 1,008 (56%) was of the opinion that it can produce world class athletes. Gender was found to slightly influence attitude (x=50.2I, std error=1.11). University type was found to influence ICT for increased sport performance significantly (x=49.06, std error-1.23). Moreover, correlation between availability and utilization of ICT tools for increased sport performance was high and significant (r=.023, p>0.05). Universities should invest in sports development by providing needed ICT tools and athletes are to sustain this attitude to improve our sport rankings in the world. Government at levels should expose athletes to international competition.